Development of a database prototype system for the local church of Nicolas Zamora - Pascua, Sonia M. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2007)
Database Management System (DBMS) has been the foremost tool in managing Information Systems (IS) today. Several approaches provide knowledge and techniques on Systems Analysis and Design (SAD). SAD has been accepted as a basic step in making a system that complies to its use and function. The user needs and demands define what design will be tailored to these specific needs. Churches have adapted SAD and DBMS in their systems. They are receptive to automation and their direct response to technology is to use this in managing their information system. The local church of Nicolas Zamora officers, particularly their secretaries, require a database management system (DBMS) to help them do their jobs with better efficiency. This should allow them to devote more time to their other concerns and responsibilities. They need a system which is custom-made according to their activities and functions in the organization.
A systems analysis was conducted, and the existing file-based system was reviewed. The design of the new DBMS was based on the expressed needs and requirements from the end users. Their IT knowledge and capabilities had been considered. Once the structure was formulated, a framework was used as a guide. Feedbacks were acquired after the presentation of the proposed design to determine the usefulness of the new DBMS and which areas had been overlook and are lacking.
The users were very satisfied with the outcome of the study. They unanimously applaud the capabilities of their new system. Their preferences have been recognized and were integrated in the proposed database. The products generated from the experimental models are expected to support the development of DBMS application among the rest of their congregation.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Church of Nicolas Zamora; Database management; Information systems management